Toxic effect and mechanism of tris (1, 3-dichloro-2-propyl)phosphate (TDCPP) on the marine alga Phaeodactylum tricornutum. (August 2020) - Liu, Qian; Tang, Xuexi; Jian, Xiaoyang; Yang, Yingying; Ma, Wenqian; Wang, You; Zhang, Xinxin
Abstract: Tris (1, 3-dichloro-2-propyl)phosphate (TDCPP) is an organophosphate-based plasticizer and flame retardant with a high production volume. The ubiquitous distribution and persistence of TDCPP in aquatic environment have led to concerns over its possible toxic effects on aquatic organism. However, data regarding the toxicity of TDCPP on algae are limited, and the molecular mechanism remains largely unknown. Therefore, we determined the growth characteristics, physiological changes and transcriptome profiles of Phaeodactylum tricornutum in response to 4 mg L −1 TDCPP for 24 h. TDCPP caused morphological damage and growth inhibition with an EC50 value of 3.71 mg L −1 at 96 h. A decline in pigments and photosynthetic activity was observed, indicating the occurrence of photosynthesis inhibition. Although the activities of both glutathione peroxidase and glutathione reductase were stimulated, oxidative stress was not relieved in the algal cells, as evidenced by the elevated levels of reactive oxygen species and lipid peroxidation. Transcriptomic analyses revealed 3312 differentially expressed genes (DEGs), and photosynthesis was a key target, as genes related to this process were greatly altered under TDCPP stress. Moreover, some DEGs were also enriched in amino acid metabolism, nitrogen metabolism, nucleotide metabolism and lipid metabolism, implying that TDCPP-induced damage towards algae by various pathways. Additionally, several TFs related to stress signaling were differentially expressed, suggesting roles in the TDCPP stress response. The results will provide critical data to understand the ecological risks and toxic mechanism of OPFRs entering into marine habitat. Highlights: TDCPP inhibited the growth of P. tricornutum. Photosynthesis may be a key TDCPP target. TDCPP induced an imbalance between ROS defense system and oxidative stress. TDCPP regulated some TFs related to stress signaling.